Producción de textos informativos en los estudiantes del cuarto grado de educación primaria - Moreno Cacha, Walter Cirilo (2018)
The importance of the environment today is undeniable and this has to do with the abuse and wear that the human being generates of way each time more notorius on the complex natural phenomena, provoking alterations to the enviromment thar affect not only to other living beings but olso to himself today the data that demonstrate the deterioration of the planet they are categorical and evident and on it there is a consent in the scientific international community. This means that the moment of starting the actionto preserve the space in which we live together from efficacious way has come._x000D_ The learning session We Elaborated a Poster on the Care of the Environment it was designed for the students of the fourth degree C of primary education of the educational institution Faith and Alegría– Huaraz has like purpose to develop in the students the capacity of writing informative texts with the intention of promoting in them the defense and preservation of the environment promoting delicate activities and protection of our natural resources._x000D_ In order to achieve this objective was used strategies of production of informative texts basing us on the previous knowledges and in the own experiences of the students, making use of a formative evaluation.